The Polar Express - Zemeckis, Robert, 1952-; Hanks, Tom.; Zemeckis, Leslie Harter; Deezen, Eddie, 1958-; Gaye, Nona, 1974-; Scolari, Peter, 1954-; Burgess, Don.; Presley, Robert; Silvestri, Alan.; Ballard, Glen.; Van Allsburg, Chris; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2005)
When a doubting young boy takes an extraordinary train ride to the North Pole, he embarks on a journey of self- discovery that shows him that the wonder of life never fades for those who believe.
Title from container.
Originally released as a motion picture in 2004.
Based on the book by Chris Van Allsburg.
Directors of photography, Don Burgess, Robert Presley ; editors, Jeremiah O'Driscoll, R. Orlando Duenas ; music, Alan Silvestri, Glen Ballard ; costume designer, Joanna Johnston ; production designers, Rick Carter, Doug Chiang.
Tom Hanks, Leslie Harter Zemeckis, Eddie Deezen, Nona Gaye, Peter Scolari, Brendan King, Andy Pellick, Josh Eli, Mark Mendonca, Rolandas Hendricks.
MPAA rating: G.
Keywords: Christmas plays; North Pole -- Drama; Feature films; Children's films; Films for the hearing impaired